2003
DOI: 10.1152/japplphysiol.00926.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in skeletal muscle fatigability are related to contraction type and EMG spectral compression

Abstract: The purposes of this study were 1) to evaluate gender differences in back extensor endurance capacity during isometric and isotonic muscular contractions, 2) to determine the relation between absolute load and endurance time, and 3) to compare men [n = 10, age 22.4 +/- 0.69 (SE) yr] and women (n = 10, age 21.7 +/- 1.07 yr) in terms of neuromuscular activation patterns and median frequency (MF) shifts in the electromyogram (EMG) power spectrum of the lumbar and hip extensor muscles during fatiguing submaximal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
5
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(172 citation statements)
references
References 47 publications
13
140
5
8
Order By: Relevance
“…The choice may be arguable but seems appropriate as physiological research confirms an association between muscle fatigue and shifts in firing rates towards lower values [7,[12][13][14][15][16][17][18][19][20]. Moreover, regression analyses between the MF and MPF slopes with time were capable of detecting differential responses in the fiber types: with slow twitch fibers showing more resistance to fatigue than the fast twitch fibers [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice may be arguable but seems appropriate as physiological research confirms an association between muscle fatigue and shifts in firing rates towards lower values [7,[12][13][14][15][16][17][18][19][20]. Moreover, regression analyses between the MF and MPF slopes with time were capable of detecting differential responses in the fiber types: with slow twitch fibers showing more resistance to fatigue than the fast twitch fibers [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of muscle fatigue: EMG power spectral frequency analysis was used to evaluate skeletal muscle endurance [12][13][14][15][16][17][18][19][20]. The median frequency (MF) and the mean power frequency (MPF)…”
Section: Stimulation Parametersmentioning
confidence: 99%
“…Some biological sex differences are well established. For example, studies have shown that men have a greater ratio of type II (fast) to type I (fatigue-resistant) muscle fibres (Mannion et al, 1997(Mannion et al, , 1998Staron et al, 2000), possibly explaining male-female differences in fatigability (Clark et al, 2003). Generally, we stress the importance of considering that gender, sex, social class, age and ethno-cultural group membership interact in various ways with WMSDs determinants (Habib and Messing, 2012;Lederer, Rivard and Mechakra-Tahiri, 2012;Premji et al, 2010;Seifert et al, 2007).…”
Section: Socio-cultural Aspects In Wmsd Developmentmentioning
confidence: 94%
“…A load cell (SF01, EMG system of Brazil Ltda. ), with a capacity of 0-200 kgf, was attached to the Roman chair with a chain and to a nylon torso harness, equipped with a ring at the mid-sternal region to measure the maximum strength of the back extensors (in Newtons: N) 21 . The participants performed three maximal voluntary isometric contractions (MVIC) of the back extensors in a horizontal position (Figure 2 (A)), with a three minute rest between trials.…”
Section: Methodsmentioning
confidence: 99%